The case for dynamic cities - Brian J. Asquith; Margaret C. Bock (W.E. Upjohn Institute for Employment Research, 2022)
Cities today are confronting never-before-seen challenges to their top spot in the economic hierarchy. In this chapter, we lay out four challenges, past and future, that cities face today and identify policies that can help address the problems we identify. We call attention to the need for many U.S. cities to redevelop the large amount of aging postwar single-family housing, while reforming past exclusionary zoning and infrastructure decisions that exacerbated inequality. Cities will have to fix these past mistakes against the backdrop of an aging population and the rise of remote working, both of which undercut cities' traditional source of growth by reducing the flow of younger and middle-aged people willing to live in urban centers. The common theme running throughout this paper is that cities, their residents and their business leaders will need to embrace a dynamic ethos and be given a freer hand to reposition their municipalities to face a future that is shaping up to be quite different from the past.
Keywords: R11; R12; R58; J10; 330; Zoning; infrastructure; housing; population aging